The Effect of YouGlish Web Tool through Shadowing Technique and Learning Motivation on EFL Students’ Pronunciation Accuracy - Reni Eka Putri; Zulhidah Zulhidah; Bukhori Bukhori (Journal of Educational Sciences, 2026)
This study investigated differences in English pronunciation accuracy among students with high, medium, and low learning motivation who were taught using the YouGlish web tool through the shadowing technique and those taught without it. It also examined the interaction effect between instructional method and learning motivation on pronunciation accuracy. Employing an experimental 2×3 factorial post-test-only design, the study involved first-semester students of the English Education Department at the State Islamic University of Sultan Syarif Kasim Riau. Two classes totaling 60 students were selected through simple random sampling. Data were collected through a pronunciation test after four treatment sessions and analyzed using two-way ANOVA. The results showed that the use of YouGlish through shadowing did not produce significant differences in pronunciation accuracy across varying levels of learning motivation. Additionally, no significant interaction effect was found between the teaching method and students’ motivation levels. Although learning motivation contributed to pronunciation performance, its effect was not statistically significant. These findings indicate that the effectiveness of YouGlish-assisted shadowing practice in improving pronunciation accuracy was not significantly influenced by students’ learning motivation, suggesting that other factors may play a more substantial role in determining pronunciation development.